Characterizing the health experience of Tuvaluan migrants in Auckland, New Zealand. Issue 4 (17th November 2021) - Emont, Jordan Paul; O'Brien, Seipua; Nosa, Vili; Toll, Elizabeth Terry; Goldman, Roberta
Abstract : Purpose: It is predicted that increasing numbers of citizens of the Pacific Island nation of Tuvalu will migrate to New Zealand in the coming decades due to the threat of climate change. Tuvaluans currently living in New Zealand face disparities in income, education and health. This study aims to understand the views of recent Tuvaluan immigrants to Auckland, New Zealand on health behaviors, health care and immigration. Design/methodology/approach: The authors conducted semi-structured interviews, key informant interviews and participant observation using a focused ethnography methodology. Findings: Participants explained that Tuvaluans in New Zealand do not fully use primary care services, have a poorer diet and physical activity compared to those living in Tuvalu, and struggle to maintain well-paying, full-time employment. Practical implications: As Tuvaluan immigration to New Zealand continues, it will be important to educate the Tuvaluan community about the role of primary health-care services and healthy behaviors, facilitate the current process of immigration and provide job training to recent immigrants to improve their opportunities for full-time employment and ensure cultural survival in the face of the threat of climate change. Originality/value: This paper contributes to a greater understanding of the challenges to be faced by Tuvaluan environmental migrants in the future and features a high proportion of study participants who migrated due to climate change.